Occupational Therapy Student-Run Free Clinic: Mutual Benefits in Expanded Homeless and Health Services and Clinical Skills Development - Drummond, Ronald; Koziol, Cassidy; Yeats, Hunter; Tyminski, Quinn (Journal of Student-Run Clinics, 2021)
Background: Evidence indicates occupational therapy (OT) services can address the unmet needs of individuals experiencing homelessness (IEH) to promote health, engagement in meaningful activities, and independent living skills. Additionally, student-run free clinics (SRFCs) are an effective method for developing clinical skills while providing needed services for the community. Based on the available evidence, a student-run OT clinic was developed in partnership with a local homeless services agency. The objective of this pilot study was to evaluate the services established in an OT SRFC in a homeless population to determine the initial effectiveness of the clinic for students and clients. It was hypothesized that the SRFC would increase student perceived clinical skills and provide mutual benefit to clients. Methods: Participants of this SRFC included 17 OT students (n=10 doctoral students, n=7 masters students) and 70 IEH since its opening in Fall 2018. OT students developed and implemented evidenced-based group and individual interventions designed to address health, wellness, and quality of life for the homeless population. Student skills competency, confidence, and client satisfaction were regularly evaluated through survey. Mann-Whitney U tests were used to determine statistical differences. Results: Results indicate that clients are satisfied with clinic services, students’ engagement, and some positive changes in independent living skills. Students reported statistically significant improvement in competency of professional behaviors (p<0.001) and interventions (p=0.003). Conclusion: Providing OT services through an SRFC is a promising approach to service delivery within the homeless population due to the mutual benefit for students to increase clinical and interpersonal skills and attitudes in preparation for entry-level practice.